Concomitant Use of Opioids and Benzodiazepines in the Outpatient Setting. Issue 4 (18th March 2019) - Simon, Jeremy; Gehret, Jeffrey; Stolzenberg, David; Beredjiklian, Pedro K.; Teng, Jonathon; Paskey, Taylor; Raju, Robin
Abstract : Background: Benzodiazepines have been identified as a concurrent factor in opioid‐related deaths. Although the dangers of concomitant administration of opioids and benzodiazepines are well documented, implementation of this knowledge into practice may be lagging behind. Objective: To examine the concomitant use of opioids and benzodiazepines in the outpatient setting. Design: Retrospective study. Setting: Academic outpatient multispecialty practice. Participants: Over 2000 outpatient clinic visits from January 2018 to April 2018 among four physiatrists were analyzed. Methods: All patients were reviewed in the Prescription Drug Monitoring Program (PDMP) website to identify whether they have filled either opioid or benzodiazepine prescription(s) in the last 12 months. Main Outcome Measurements: Number of opioid and benzodiazepine prescriptions, discrepancies in reporting of medications, providers prescribing medications, and cigarette/alcohol use. Results: A total of 353 patients were identified to have filled either opioid or benzodiazepine prescription(s) in last 12 months. 49.4% of patients prescribed opioids were found to be taking benzodiazepines concurrently. Reporting discrepancies were noted between the outpatient electronic medical record and PDMP in 17.2% of patients. Among patients taking both opioids and benzodiazepines, 38.9% had multiple providers prescribing these medications, 41.9% were over 65 years old, and 11.9% were daily cigarette/alcohol users. Patients taking both types of drugs (opioids and benzodiazepines) were significantly more likely to use different providers (38.9%) compared to patients taking one type of drug (9.8%, P < .001). The former group was also noted to fill significantly more prescriptions than the latter group ( P < .001). Conclusion: The study results emphasize that clinicians may not be aware that some of their patients are concurrently taking opioids and benzodiazepines. These results highlight the importance of routinely checking the PDMP and using that information to make fully informed decisions to minimize risks in use of these controlled substances. Level of Evidence: III